2019
DOI: 10.1002/anie.201814143
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Reaction of Silacyclobutanes with Unactivated Alkynes to Afford Silacyclohexenes

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(36 citation statements)
references
References 97 publications
1
33
0
2
Order By: Relevance
“…The unexpected result of 2 d suggested that the silyl protecting group might take a role in the reaction, of which we have no understanding at this point. The bulkiness of TIPS, which shields the C≡C bond, [21] as well as the inductive electron‐donation effect from silyl group [21] are probably the reasons for the observed direct silylation, which is utterly different than the [4+2] cycloaddition under very similar conditions reported by Song and co‐workers [17i] . In addition, we also attempted the enantioselective variants of this reaction by using chiral BINAP ligands.…”
Section: Methodsmentioning
confidence: 64%
“…The unexpected result of 2 d suggested that the silyl protecting group might take a role in the reaction, of which we have no understanding at this point. The bulkiness of TIPS, which shields the C≡C bond, [21] as well as the inductive electron‐donation effect from silyl group [21] are probably the reasons for the observed direct silylation, which is utterly different than the [4+2] cycloaddition under very similar conditions reported by Song and co‐workers [17i] . In addition, we also attempted the enantioselective variants of this reaction by using chiral BINAP ligands.…”
Section: Methodsmentioning
confidence: 64%
“…To the best of our knowledge, only Shintani, Hayashi, Nozaki et al and Song have succeeded in forming six-membered tetraorgano-substituted silicon-stereogenic silanes (Fig. 1b) [36][37][38][39][40] , while the construction of Si-chirality on six-and seven-membered triorgano-substituted monohydrosilanes via asymmetric catalysis is still unknown to date, which is presumably due to a lack of general and e cient synthetic methods. Given the increasing demand for the synthesis of novel functional-materials-oriented silicon-bridged biaryls, construction of six-or seven-membered monohydrosilanes in a chiral version is highly attractive.…”
Section: Introductionmentioning
confidence: 99%
“…16 Due to their high ring strain and Lewis acidity, SCBs are often used as precursors to other organosilicon compounds through ring opening/expansion reactions catalysed by transition metals. 16,17 Even though ring expansion of SCBs can also provide silacyclopentanes under specific conditions, the most direct method for their synthesis consists in the addition of metal treated 1,3-butadienes to dichlorosilanes. 18,19 The synthesis of silacyclopentenes through palladium-catalysed silylene-1,3-diene [4 + 1] cycloaddition 20 allows flexibility on substitution of the cyclopentene core.…”
Section: Introductionmentioning
confidence: 99%